1995
DOI: 10.1111/j.1476-5381.1995.tb16638.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of action of α2‐adrenoceptors in human isolated subcutaneous resistance arteries

Abstract: pertussis toxin inhibited responses to azepexole, but had no significant effect on tone induced by KPSS or noradrenaline. ETYA, an inhibitor of phospholipase A2, lipoxygenase and cyclo-oxygenase, had no effect on azepexole-induced contraction in the presence of NW nitro-L-arginine methyl ester. 6 Azepexole, a selective a2-adrenoceptor agonist, contracts human subcutaneous resistance arteries by a mechanism largely dependent on the influx of extracellular Ca2", probably through voltage-operated calcium channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Studies on vascular smooth muscle cells have shown that α 2 -adrenoceptor activation increases intracellular calcium levels (Chotani et al, 2004), and pertussis toxinsensitive, G i -mediated activation of L-type calcium channels has been suggested as a mechanism (Hughes et al, 1996;Lepretre & Mironneau, 1994;Mironneau & Macrez-Lepretre, 1995). The existence of such a pathway was confirmed in studies using isometric tension measurements on blood vessels (Parkinson & Hughes, 1995;Roberts, 2001), and elevated intracellular calcium levels are indeed needed for pMLC 20 formation (Aburto et al, 1993). Our current results are in agreement with these proposed mechanisms, as blocking the activation of G i -proteins with pertussis toxin resulted in almost complete abolishment of the pMLC 20 response evoked by dexmedetomidine, and addition of the L-type calcium channel blocker nifedipine resulted in a 66% decrease of pMLC 20 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Studies on vascular smooth muscle cells have shown that α 2 -adrenoceptor activation increases intracellular calcium levels (Chotani et al, 2004), and pertussis toxinsensitive, G i -mediated activation of L-type calcium channels has been suggested as a mechanism (Hughes et al, 1996;Lepretre & Mironneau, 1994;Mironneau & Macrez-Lepretre, 1995). The existence of such a pathway was confirmed in studies using isometric tension measurements on blood vessels (Parkinson & Hughes, 1995;Roberts, 2001), and elevated intracellular calcium levels are indeed needed for pMLC 20 formation (Aburto et al, 1993). Our current results are in agreement with these proposed mechanisms, as blocking the activation of G i -proteins with pertussis toxin resulted in almost complete abolishment of the pMLC 20 response evoked by dexmedetomidine, and addition of the L-type calcium channel blocker nifedipine resulted in a 66% decrease of pMLC 20 .…”
Section: Discussionmentioning
confidence: 86%
“…This phosphorylates myosin light chains, allowing these to form cross-bridges with actin filaments, which is the molecular basis of smooth muscle cell contraction (Small & Sobieszek, 1977;Somlyo & Somlyo, 1968). Most studies on α 2 -adrenoceptor-mediated vascular smooth muscle contraction have employed isometric tension measurements on blood vessels, and the results have varied greatly depending on the luminal diameter of the vessel and its anatomical origin, with α 2 -adrenoceptors being more prominent in small arteries and veins but not in large arteries such as the aorta (Nielsen et al, 1989;Parkinson & Hughes, 1995;Roberts, 2001Roberts, , 2003. In particular, the vascular responses relating to dexmedetomidine appear to be very complex; in endotheliumdenuded arteries, the drug has induced contraction, whereas in intact vessels the relaxing and contracting effects of dexmedetomidine appear to oppose each other (Kim et al, 2009;Wong, Man, Vanhoutte, & Ng, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous agonist noradrenaline can cause vasoconstriction via both cq-and c~2-adrenoceptors (Timmermans et al 1987). Concomitant vasoconstriction via both cq-and c~2-adrenoceptors has also been shown in human subcutaneous microvessels (Parkinson and Hughes 1995). A possible concomitant activation of fl-adrenoceptors is not relevant for the interpretation of the present data since our experiments were routinely performed in the presence of a high concentration of the/7-adrenoceptor antagonist propranolol.…”
Section: Discussionmentioning
confidence: 69%
“…However, in the porcine palmer lateral vein, Wright et al [144] found that contractions evoked by α 2 -adrenoceptor agonists only involved reduction in cAMP when cAMP levels were elevated by agents that stimulate adenylate cyclase. In human subcutaneous resistance vessels, pertussis-toxin-sensitive contractions to α 2 -adrenoceptor agonists were found to involve an influx of Ca 2+ [107]. α 2 -Adrenoceptors may also be linked to phospholipase A 2 [107].…”
Section: Cellular Responses Mediated By Adrenoceptors In Smooth Musclementioning
confidence: 97%
“…In human subcutaneous resistance vessels, pertussis-toxin-sensitive contractions to α 2 -adrenoceptor agonists were found to involve an influx of Ca 2+ [107]. α 2 -Adrenoceptors may also be linked to phospholipase A 2 [107].…”
Section: Cellular Responses Mediated By Adrenoceptors In Smooth Musclementioning
confidence: 97%